Daniel Danis en traduction : problèmes de traduction du Chant du Dire-Dire en espagnol chilien - Kristić, Andrea Pelegrí (Theatre Research in Canada / Recherches théâtrales au Canada, 2014)
This article offers a study of the Chilean translation of Daniel Danis’s play Le Chant du Dire-Dire, which was produced in accordance with the functionalist principles of the skopos theory of translation (Vermeer 1978). This approach subordinates the translation of a text to the function (or the skopos) that is assigned to the target text, defined in conformity with the target text’s own communicational context and consistent with its purpose and addressees. This skopos facilitates the establishment of a concrete translation plan that defines the translation choices. For its flexibility, this article proposes this theory as an efficient methodological alternative for the translation of this stylistically and aesthetically complex play. In particular, the translation plan presents a “third way” between a “literary” translation [littérarité : that is, formal and linguistic properties of a text that distinguish it from other kinds of texts as “literature”] and the play’s adaptation to a Chilean context; rather, the translation results in a Chilean version that attempts to retain the stylistic particularities and the expressive inventions found within Danis’s play [its littérarité].